2020
DOI: 10.1590/0103-6513.20190108
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities for sustainable innovation: the case of a footwear company in Brazil

Abstract: Paper aims: This paper aims to investigate which dynamic capabilities are responsible for sustainable innovation. Originality: Based on the literature review, we propose a theoretical framework that relates dynamic capabilities to sustainable innovation (considering triple bottom line perceptive), regarding product, process marketing, and organizational innovations typologies. Research method: The framework was applied in this research through a case study method in two plants of a large footwear company that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…as novel methods to develop strategy and structure in the organization, change the enterprise management procedures and motivate and recompense. (Rodrigues et al, 2020) found out that management innovation is negatively linked with the firm's performance but mediated by performance management. Quality assurance initiatives such as ISO 9001 include "hard" and "soft"' components, which aligned with the organization's opposing mechanistic versus ecological views.…”
Section: Management Innovation Ability and Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…as novel methods to develop strategy and structure in the organization, change the enterprise management procedures and motivate and recompense. (Rodrigues et al, 2020) found out that management innovation is negatively linked with the firm's performance but mediated by performance management. Quality assurance initiatives such as ISO 9001 include "hard" and "soft"' components, which aligned with the organization's opposing mechanistic versus ecological views.…”
Section: Management Innovation Ability and Financial Performancementioning
confidence: 99%
“…New administrative structures, organizational processes, supervisory procedures, developments, and systems that could create value for the company are managerial novelties ( (Birkinshaw, Hamel, & Mol, 2008)). (Rodrigues, Gohr, & Calazans, 2020) the internal absorption capacity, internal knowledge resources, and capabilities, (Y. S. Chen, Chang, & Wu, 2012) environmental leadership, culture, and environmental capabilities, (Huang & Li, 2017) found out that when managers consider natural environment problems as an advantage, the constructive environmental approach is more likely to be taken, which can boost the environmental efficiency and financial performance of the business.-focusing on Johannesburg Stock Exchange-listed manufacturing firm. Following the studies of (García-Granero, Piedra-Muñoz, & Galdeano-Gómez, 2018)stated that many types of research on eco-innovation, sustainability, and green innovation are done in Europe, with Spain leading the rank in the article.…”
Section: Introductionmentioning
confidence: 99%
“…This paper contributes to improve the body of knowledge about innovation activities for sustainability in HEIs from the perspective of DC through the identification of microfoundations that drive SOI within these institutions and assist in a more efficient use of resources, environmental conservation, and improvement of the social environment (Inigo & Albareda, 2019;Rodrigues et al, 2020;Teece, 2007). In practical terms, this article helps HEI managers to understand which DC microfoundations enable sustainability-oriented innovations in HEI environments.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the ability to renew tangible and intangible assets is extremely relevant for business competitiveness in economic, environmental, and social terms (Beuter et al, 2019;Teece et al, 1997). Therefore, sustainability is regarded as one of the main drivers of innovation (Rodrigues et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The literature brings examples that industrial clusters are a fertile inter-organizational network that promotes innovation (Porter, 1998; Romijn and Albaladejo, 2002; Wonglimpiyarat, 2006; Silvestre and Dalcol, 2009; Antolin-Lopez et al , 2015; Strand et al , 2017; Chandrashekar and Hillemane, 2018; Elche et al , 2018; Bittencourt et al , 2019). As a consequence, industrial clusters are increasingly gaining attention from researchers and policy makers worldwide to understand the drivers of innovations in this collaborative network (Chandrashekar and Hillemane, 2018; Faustino et al , 2019; Rodrigues et al , 2020; Tavares et al , 2021).…”
Section: Introductionmentioning
confidence: 99%